QSAR Studies of 2-Aroylindole Derivatives: Tubulin Inhibitors in Cancer Therapy - Prakash B.N. Gupta, Surya; Upmanyu, Neeraj; Hari Narayan Moorthy, N.S.; Bhattacharya, S. (Asian Journal of Chemistry, 2010)
QSAR study was used to relate the tubulin inhibitory activity of 2-Aroylindole derivatives with various physicochemical descriptors. Stepwise multiple regression analysis was performed to find out the correlation between various physicochemical descriptors and biological activity of the compounds by using Openstat 2 version 6.5.1 and Valstat statistical software. Out of several equations developed, the best equations having highest significance were selected for further studies, which are mentioned below: –log IC50 = 0.0604 (±0.222)R6 – 0.479(±0.239)π – 0.781(±0.455)HD – 0.163(±0.147)HA – 0.018(±0.304) n = 25; r = 0.812; r2 = 0.659; F = 9.707; s = 0.236 (1) –log IC50 = 0.565 (±0.240)R6 – 0.367(±0.217)π – 0.723(±0.493)HD – 0.318 (±0.472)F – 0.138(±0.297) n = 25; r = 0.782; r2 = 0.612; F = 7.900; s = 0.252 (2) The results obtained from QSAR studies indicate that in both the equations, the hydrogen donor, field effects and hydrophobic descriptors contributed negatively to the biological activity. In eqn. (1), the indicator variable at R6 position of the parent nucleus positively contributes to the activity. But in eqn. (2), R6 positively and field effect negatively contributes along with hydrogen donor. Both the equations have 95% significance and the F value is 9.707 and 7.900 respectively suggests that the equations have very good predictive power.